Fire-sale FDI or business as usual? - Ron Alquist; Rahul Mukherjee; Linda Tesar (Bank of Canada, 2013)
Using a new data set, we examine the characteristics and dynamics of cross-border mergers and acquisitions during emerging-market financial crises, that is, so-called fire-sale FDI. Our findings shed fresh light on whether the transactions undertaken during crisis periods differ in fundamental ways from those undertaken during more tranquil periods. The increase in foreign acquisitions during crises is mainly driven by non-financial acquirers targeting firms in the same industry rather than foreign financial firms. This increase in acquisition activity in a given industry is unrelated to the industry's dependence on external finance. There is also no evidence of an increase in the size of stakes bought during crises. In terms of the effect of crises on emerging-market mergers and acquisitions, we find little evidence that foreign acquisitions are resold, or flipped, more frequently than domestic acquisitions. Moreover, flipping rates are uncorrelated with the industry's dependence on external finance. Finally, the probability of being flipped to a domestic buyer does not differ across crisis and non-crisis periods. All of these results are robust to alternative empirical specifications, different definitions of crises, and the inclusion of macroeconomic controls. Contrary to conventional wisdom, fire-sale FDI and asset flipping by foreign firms appear to have been business as usual.
Keywords: G01; G34; 330; Financial markets; International financial markets; International topics